Radioresistance of cancer stem‐like cell derived from canine tumours. (28th July 2014) - Tanabe, A.; Deguchi, T.; Sato, T.; Nemoto, Y.; Maruo, T.; Madarame, H.; Shida, T.; Naya, Y.; Ogihara, K.; Sahara, H.
Abstract: Cancer stem‐like cells (CSCs)/cancer‐initiating cells (CICs) are a small subpopulation of cancer cells that are responsible for the initiation, recurrence and metastasis of cancer. We previously demonstrated that, using the Hoechst 33342 dye‐based side population technique, CSCs/CICs in canine lung adenocarcinoma cell line exist. In this study, as CSCs/CICs are known to form spheres in anchorage‐independent environment in vitro, we evaluated the stemness of spheroid cells derived from canine lung adenocarcinoma and osteosarcoma cells by expression of stemness markers, and investigated radioresistance. Spheroid cells showed greater expression of stemness markers Oct‐4 and CD133 gene than those of adherent‐cultured cells. In nude mouse xenograft models, spheroid cells showed higher tumourigenic ability than adherent‐cultured cells. In addition, spheroid cells showed significantly resistant against radioactivity as compared with adherent‐cultured cells. These results suggest that spheroid cells could possess stemness and provide a CSCs/CICs research tool to investigate CSCs/CICs of canine tumour cells.